Forecasting probability of multiorgans insufficiency syndrome development in patients with a peritonitis - D. V. Alekseyev (Бюллетень сибирской медицины)
Investigation of the indices, characterizing a functional condition of the hemostasis in patients with peritonitis, to takes more reliable trend forecasting a development of the multiorgans insufficiency syndrome and unfavorable outcome of the disease, tran research of hemodynamic and autointoxication states.